Alterations in the social-conditioned place preference and density of dopaminergic neurons in the ventral tegmental area in Clsnt2-KO mice - I. N. Rozhkova; S. V. Okotrub; E. Yu. Brusentsev; K. E. Uldanova; E. A. Chuyko; V. A. Naprimerov; T. V. Lipina; T. G. Amstislavskaya; S. Ya. Amstislavsky (Вавиловский журнал генетики и селекции)
The incidence of autistic spectrum disorders (ASD) constantly increases in the world. Studying the mechanisms underlying ASD as well as searching for new therapeutic targets are crucial tasks. Many researchers agree that autism is a neurodevelopmental disorder. Clstn2-KO mouse strain with a knockout of calsyntenin 2 gene (Clstn2) is model for investigating ASD. This study aims to evaluate the social-conditioned place preference as well as density of dopaminergic (DA) neurons in the ventral tegmental area (VTA), which belongs to the brain reward system, in the males of the Clstn2-KO strain using wild type C57BL/6J males as controls. Social-conditioned place preference test evaluates a reward-dependent component of social behavior. The results of this test revealed differences between the Clstn2-KO and the control males, as the former did not value socializing with the familiar partner, spending equal time in the isolationand socializing-associated compartments. The Clstn2-KO group entered both compartments more frequently, but spent less time in the socializingassociated compartment compared to the controls. By contrast, the control males of the C57BL/6J strain spent more time in socializing-associated compartment and less time in the compartment that was associated with loneness. At the same time, an increased number of DA and possibly GABA neurons labeled with antibodies against the type 2 dopamine receptor as well as against tyrosine hydroxylase were detected in the VTA of the Clstn2-KO mice. Thus, a change in social-conditioned place preference in Clstn2-KO mice as well as a higher number of neurons expressing type 2 dopamine receptors and tyrosine hydroxylase in the VTA, the key structure of the mesolimbic dopaminergic pathway, were observed.